"The Controversy About Civic Education in Spain" - Rico Motos, Carlos Miguel (My University)
La introducción de la educación para la ciudadanía en el sistema escolar español ha dado lugar a una fuerte polémica con sectores conservadores de la sociedad española, que afirman que la educación moral de los estudiantes es una competencia exclusiva reservada a las familias. Contestando a estas críticas, este artículo señala las razones que justifican el contenido sustantivo de la materia y la competencia del gobierno democrático en lo que respecta a la educación cívica.

The introduction of Education for Citizenship into the Spanish school system has given rise to a strong controversy with conservative actors in Spanish society who claim that the students moral education is an exclusive realm reserved for families. Challenging these criticisms, this article points to the reasons that justify both the substantive content of the subject and the competence of democratic government with regard to civic education.
Artículos en revistas